Web form design checklist based on the three-layer model (TLM) - Norshuhada Shiratuddin; Zanariah Idrus (Penerbit UKM, 2007)
The objectives of end users visiting web site are generally for information retrieval whereas for web application, users have specific goals, which are to complete tasks successfully. Nevertheless, some online job applications do not meet task-based orientation design and this resulted in users’ frustration. Therefore, for the purpose of reducing the frustration and providing guidelines, a form design checklist based on the Three-Layer Model (TLM) was developed. In addition, an investigation of the current state of web form design among developers in Malaysia was also conducted. A four-step methodology was followed; understand the TLM concept, develop checklist based on guidelines, collect and identify existing Malaysian web forms, and finally, validate the checklist and compare the collected web forms with the three-layer model. In validating the checklist, 15 respondents performed three sets of tasks: pre-TLM, post-TLM and comparing of three pre-selected online forms. Findings indicated that participants designed better web forms after learning about the TLM and this suggests that the checklist provided guidance in designing better web form. Results also pointed out that the current state of web form designed by Malaysian seems to suggest that it does not meet task-based orientation design.